Education in spite of policy - Alexander, Robin J. 1941- (Routledge, Taylor & Francis Group, 2022)
"A national system of education cannot function without policy. But the path to practice is seldom smooth, especially when ideology overrules evidence or when ministers seek to micromanage what is best left to teachers. And once the media join the fray the mixture becomes downright combustible. Drawing on his long experience as teacher, researcher, government adviser, campaigner and international consultant, and on over 600 published sources, Robin Alexander expertly illustrates and illuminates these processes. This selection from his recent writing, some hitherto unpublished, opens windows onto cases and issues that concern every teacher. Part 1 tackles system-level reform. It revisits the Cambridge Primary Review, an evidence-rich enquiry into the condition and future of primary education in England, which challenged the UK government's policies on curriculum, testing, standards and more besides.
Keywords: Education and state / England; Cambridge Primary Review (Organization); Education / Curricula / England; Effective teaching / England; Programme for International Student Assessment; Education and state; Education / Curricula; Effective teaching; England